The Influence of Sales and Operation Costs on Profitability (A case study at UB Opaset Perum Bulog Divre Jateng) - Revi - Pramadefa; Sri - Marhaeni; Umar - Farouk (Politeknik Negeri Semarang, 2021)
The aim of this study was to determine the influence of sales and operation costs on profitability of UB OPASET Perum BULOG Divre Jateng in period 2016-2018, both partially and simultaneously. The study utilized quantitative research method. The datasources was collected from UB OPASET Perum BULOG Divre Jateng. Regarding the use of period, the total data which used was thirty six months. The study explored with multiple linear regression statistical analysis, along with descriptive analysis and classical assumption test namely normality test, heteroskedasticity test, multicollinearity test, autocorrelation test, and linearity test. The F-Test stated that sales and operation costs had significant influence simultaneously. Based on the determinant coefficient, the variable of sales and operation costs influenced profitability by 64.2%. Meanwhile, the remaining 35.8% was explained by another variable that was not examined in this study. Based on the t-Test result found that sales had significant positive influence on profitability (ROA) partially. While, operation costs had partial significant negative influence on profitability (ROA)